O senhor da guerra : Ricardo Coração de Leão e a ressignificação da Guerra Santa na Terceira Cruzada (1189-1192) - Souza, Jario Sena (2022)
This paper aims to analyze the Third Crusade under the trajectory of Richard I (the Lionheart). The time frame follows the chosen historical subject from his birth (1157) to his return to England (1192). We discussed the political, economic and social aspects that contributed to the growth of the 'Lionheart' as king. To be able to dissect these points, we analyzed the writings of the chroniclers and their accounts of the character and the events surrounding the third crusade. During the analysis of those sources, we were able to establish recurrent political attitudes, which we call political pragmatism, which was used as a mechanism in the midst of political urgency in feudal relations. We also analyzed the wars practiced by Richard I in England, before he left for the third crusade. With this, we acknowledge that, unlike several historiographies that defend a political and military anarchism in the Middle Ages, the wars were rational and organized. Both political pragmatism and the organization of warfare were present in the religious war in the third crusade. The bibliography, to cover all these issues, ranges from classical accounts to more recent discussions: On the life of Richard I, we rely on the English historian John Gillingham, who helped us understand the young king's growth. In Jean Flori, we were introduced to the construction of the idea of Religious/Holy War, with Sean McGlynn the concept of a rational war in the Middle Ages. And finally, for the organization of the crusade, we relied on Christopher Tyerman. The chroniclers used was Rogerio de Hovenden and Ricardo Devizes.